Rate of Overlap between ICD-11 Gaming Disorder and DSM-5 Internet Gaming Disorder along with Turkish Reliability of the Gaming Disorder Scale for Adolescents (GADIS-A) - Mustafa Tuncturk; Gul Karacetin; Cagatay Ermis; R. Ogulcan Ciray; Merve Can; Celal Yesilkaya; Ayca Atay; Gokce Elif Alkas; Damla Kasap; Omca Guney; Sezen Alarslan; Burak Cakir; et al. (Dubai Medical Journal)
Introduction: The main aims of the current study were (i) to explore the overlap between Internet gaming disorder (IGD) and gaming disorder (GD) diagnoses, (ii) to identify clinical characteristics in clinical settings, and (iii) to measure psychometric properties of the Gaming Disorder Scale for Adolescents (GADIS-A). Methods: 222 adolescents who were followed up within a tertiary-care mental health hospital, were included (IGD/GD group [n = 111], clinical comparison group [n = 90], healthy controls [n = 21]). The tools used were the GADIS-A, Internet Gaming Disorder Scale – Short-Form, The Difficulties in Emotion Regulation Scale (DERS-36), Children’s Global Assessment Scale, and a semistructured interview for DSM-5 diagnoses. Results: The overlap rate of IGD and GD is 73%. Comorbid ADHD diagnoses were more commonly found in the IGD group compared to the clinical comparison group. Patients who met GD and IGD diagnoses revealed higher scores in DERS-36. Turkish GADIS-A Item-total score correlation coefficients were between 0.627 and 0.860. In the sample, there was a high level of correlation between the number of DSM-5 and ICD-11 diagnostic criteria met and GADIS-A scale scores. The Cronbach’s alphas if item deleted ranged between 0.942 and 0.954. In addition, treatment refusal was more frequent in the IGD group than in the clinical comparison group. Conclusion: The GADIS-A had good to excellent psychometric properties in Turkish adolescents. Despite having a stricter diagnostic criterion, GD overlapped with IGD in a clinical population.